Penerapan Teknik Vokal Intonasi Dalam Menyanyikan Lagu Buku Zinuno No 232 “No Somuso Todo Ndrao - Shinta Nifati K. Zebua; Robert K A. Simangungsong; Roy J. M. Hutagalung; Testi Bazarni Zebua; Tahadodo Waruwu (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to find out about vocal intonation techniques. Several things that must be paid attention to when singing are vocal techniques such as breathing techniques, articulation, expression and intonation and also signs of dynamics contained in the song. Intonation is the cooperation between tone, stress, duration and stops that accompany a speech, from the beginning to the last stop. This research uses qualitative research with data collection instruments, interviews and documentation. In the song No Somuso Todo Ndrao, it is sung with a tempo of MM=100 (Moderato), has 17 bars and uses quarter and eighth notes with a 6/8 time signature and there are several dynamic signs including p (piano), mf (mezzo forte), f (forte),Cresecendo( < ) Descrescendo ( > ) The researcher chose song No. 232 "No Somuso Todo Ndrao" because this song has the theme of letting go of sin and according to the history of the song, the lyrics of the song written by William Hunter and the notes composed by John H. Stockton are sung with joy. This song has been translated into various languages, including Nias. In singing the song Buku Zinuno no. 232 "No Somuso Todo Ndrao" the author found several problems, namely lack of precise vocal technique in singing the song, lack of accuracy in tempo, dynamics, articulation, pronunciation. Because this song tells about the release of sin, this song is often sung at a slow tempo, and lacks the use of intonation techniques when sung. Therefore, researchers are interested in applying vocal intonation techniques to the Adolescent and Youth Commission when singing this song.